Lipopolysaccharide induced mouse depression model can better simulate changes in peripheral blood FFAs in alMDD - Jincai Pan; Guanxi Liu; Yuyuan Wang; Yuting Lan; Yanmei Liang; Weicheng Li; Kexin Zhu; Yanling Zhou; Yuping Ning (PLoS ONE, 2026)
Numerous studies have highlighted a strong association between free fatty acids (FFAs) and major depressive disorder (MDD), however, the underlying mechanisms remain poorly understood. Here, we demonstrate that peripheral blood FFAs levels are significantly reduced in adolescent patients with MDD (alMDD), as quantified by gas chromatography–mass spectrometry (GC-MS), providing critical insights for preclinical depression research. Both chronic social defeat stress (CSDS) and lipopolysaccharide (LPS) models induced depression-like behaviors and triggered varying degrees of variant expressions in peripheral blood FFAs in mice. Specifically, the LPS-induced model generally exhibited superior fidelity in recapitulating the items of FFAs profile of MDD patients. Notably, hexanoic acid (C6:0), nonanoic acid (C9:0) and nonadecylic acid (C19:0) levels in CSDS mice showed closer alignment with those in alMDD individuals, whereas, cis-9-palmitoleic acid (C16:1), and myristic acid (C14:0) levels in LPS mice more accurately simulated the FFAs alterations observed in alMDD. Collectively, this study identifies the LPS-induced depression-like model as a more reliable proxy for investigating FFAs dysregulation in alMDD.